Porous graphite material and preparation method thereof
By using calcined asphalt coke as aggregate in the preparation process of porous graphite materials, combined with uniform mixing of fine binder and fluffing agent and secondary grinding process, the existing porous graphite materials have been solved by using low mechanical strength and pore distribution in the existing porous graphite materials. The problem of unevenness is obtained, and a high-performance porous graphite material is obtained.
Patent Information
- Application Number
- CN202411610885.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The existing porous graphite materials have problems such as uneven pore distribution, many internal defects and low mechanical strength, which cannot meet the application needs of high-end fields.
Use the calcined asphalt coke after grinding as aggregate, and the fine binder grinding particles are fully and uniformly mixed with the aggregate powder and fluffing agent, combined with the secondary grinding process and isostatic molding to accurately control the material. Pore size, pore size distribution and porosity.
The obtained porous graphite material has high mechanical strength, narrow pore size distribution, uniform pore distribution, and no internal defects, filling the gap in high-performance porous graphite materials.
Smart Images

Figure CN119390473A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of graphite materials, in particular to the technical field of porous graphite materials. Background Art
[0002] Porous graphite materials have a special pore structure, large specific surface area, and high porosity. They can be used as electrode materials for energy storage devices such as supercapacitors and lithium-ion batteries, catalyst carrier materials, adsorption materials for wastewater and waste gas treatment, air bearing processing materials, and control materials for the growth of silicon carbide semiconductor crystals. They have important application value. At present, existing porous graphite materials generally have shortcomings such as uneven pore distribution, many internal defects, and low mechanical strength, which cannot meet the application requirements of high-end fields such as semiconductors and air flotation pads. Summary of the invention
[0003] In view of the defects of the prior art, the purpose of the present invention is to propose a new porous graphite material and a preparation method thereof. The preparation method can accurately control the pore size, pore size distribution and porosity of the material. The obtained porous graphite material has high mechanical strength, narrow pore size distribution, uniform pore distribution and no internal defects, filling the gap in high-performance porous graphite materials.
[0004] The technical solution of the present invention is as follows: A method for preparing a porous graphite material, comprising: (1) Grinding the calcined asphalt coke to obtain aggregate powder, grinding the asphalt to obtain a binder, and grinding the dry starch to obtain a bulking agent; (2) kneading the aggregate powder with the first part of the binder to obtain a first paste, and kneading the bulking agent with the second part of the binder to obtain a first coating material; (3) grinding the first paste to obtain a second paste, and grinding the first coating material to obtain a second coating material; (4) mixing the second paste and the second coating material to obtain compressed powder; (5) isostatically pressing the pressed powder to obtain a green body; (6) calcining the green body to obtain a porous carbon material; (7) The porous carbon material is graphitized to obtain a porous graphite material.
[0005] In the above technical scheme of the present invention, the ground calcined asphalt coke is used as aggregate, which can play a significant role in material reinforcement. The finer binder powder particles are fully and evenly mixed with the aggregate powder and the fluffing agent through kneading, and can be evenly coated on the surface of the aggregate powder or the fluffing agent during the melting process, thereby enhancing the bonding strength between the aggregate powder or the fluffing agent particles. Aggregate powder and the fluffing agent are kneaded with the binder respectively, and the surfaces of the second paste and the second coating material obtained after re-grinding can form a good binder coating, and the affinity between the particles is stronger, which can significantly enhance the strength of the final material.
[0006] In the above technical scheme of the present invention, the selected bulking agent has a low residual carbon rate and can form good pores after roasting. By controlling the particle size of the bulking agent, the pore size of the corresponding size can be accurately obtained. Generally, a narrower bulking agent particle size distribution can obtain a narrower distribution of pores.
[0007] The above technical scheme of the present invention adopts a secondary grinding process, which can accurately control the second paste particles and the second coating material particles, so that they are fully mixed and the mixed pressed powder components are uniform. The subsequent isostatic pressing can ensure the uniformity of the pore distribution inside the material. At the same time, the bulking agent particles can be evenly distributed in the material, uniform pores and pore channels can be generated during the roasting process, and the decomposition products of the binder and the bulking agent can be discharged smoothly, which significantly reduces the probability of defects inside the material.
[0008] According to some preferred embodiments of the present invention, the D50 particle size of the aggregate powder is 15-20 μm.
[0009] According to some preferred embodiments of the present invention, the D50 particle size of the binder is 8-12 μm.
[0010] According to some preferred embodiments of the present invention, the D50 particle size of the bulking agent is 20-50 μm.
[0011] According to some preferred embodiments of the present invention, the D50 particle size of the second paste is 50-150 μm.
[0012] According to some preferred embodiments of the present invention, the D50 particle size of the second coating material is 20-70 μm.
[0013] The above preferred embodiments of the present invention, by controlling the size and distribution of the particle size of each component, can not only make the particles of each component more uniform, but also improve the uniformity inside the material and the uniformity of the pore distribution, thereby reducing the generation of defects. Among them, by controlling the size and distribution of the fluffing agent particles, the purpose of controlling the pore diameter and distribution can be achieved.
[0014] According to some preferred embodiments of the present invention, in the first paste, the mass content ratio of the aggregate powder to the first part of the binder is 50-65%:50-35%.
[0015] According to some preferred embodiments of the present invention, in the first coating material, the mass content ratio of the bulking agent to the second part of the binder is 75-85%:25-15%.
[0016] According to some preferred embodiments of the present invention, in the compressed powder, the mass content ratio of the second paste to the second coating material is 30-65%:70-35%.
[0017] According to some preferred embodiments of the present invention, the calcined asphalt coke has an ash content of ≤0.3%, a moisture content of ≤0.1%, a volatile matter content of ≤0.5%, and a carbon content of ≥99%.
[0018] According to some preferred embodiments of the present invention, the asphalt has an ash content of ≤0.2%, a moisture content of ≤0.2%, a quinoline insoluble content of ≤5%, and a softening point of 110-125°C.
[0019] According to some preferred embodiments of the present invention, the kneading of obtaining the first paste includes: dry mixing the aggregate powder until the dry mixing temperature reaches above 180°C, adding the first part of the binder, wet mixing at 220-250°C for 1-2h, and then cooling to obtain the first paste.
[0020] According to some preferred embodiments of the present invention, the kneading of obtaining the first coating material includes: dry mixing the bulking agent until the dry mixing temperature reaches above 220°C, adding the second part of the binder, wet mixing at 220-240°C for 0.5-1h, and then cooling to obtain the first coating material.
[0021] According to some preferred embodiments of the present invention, the volatile matter content of the first paste obtained after kneading is 12-15%.
[0022] According to some preferred embodiments of the present invention, mixing the second paste with the second coating material comprises: adding the second paste and the second coating material into a V-type mixer and mixing for 1-1.5 hours.
[0023] According to some preferred embodiments of the present invention, the isostatic pressing comprises: placing the pressed powder into a rubber film sleeve, sealing it, and then evacuating it, and then pressing it through an isostatic press.
[0024] According to some preferred embodiments of the present invention, the isostatic pressing pressure is 130-150 MPa.
[0025] According to some preferred embodiments of the present invention, the calcining comprises: placing the green body into a calcining crucible filled with yellow sand, and then calcining in a calcining furnace.
[0026] According to some preferred embodiments of the present invention, the calcination includes: at 4.0-4.5Mpa, heating from room temperature to 200°C at a heating rate of 10-20°C / h, then heating from 200°C to 350°C at a heating rate of 2-4°C / h, then heating from 350°C to 550°C at a heating rate of 3-5°C / h, heating from 550°C to 750°C at a heating rate of 6-8°C / h, heating from 750°C to 950°C at a heating rate of 8-12°C / h, keeping at 950°C for 6-12h, then cooling from 950°C to 600°C at a cooling rate of 30-50°C / h, and then naturally cooling to room temperature.
[0027] According to some preferred embodiments of the present invention, the graphitization treatment includes: heating from room temperature to 750°C at a heating rate of 80-120°C / h, heating from 750°C to 1350°C at a heating rate of 50-80°C / h, heating from 1350°C to 1600°C at a heating rate of 30-50°C / h, heating from 1600°C to 1900°C at a heating rate of 15-30°C / h, heating from 1900°C to 2400°C at a heating rate of 50-80°C / h, and keeping warm for 4-6h, followed by natural cooling.
[0028] The hot pressing and calcining scheme of the present invention can effectively improve the coking value of the binder and enhance the material strength. At the same time, in the critical temperature stage of decomposition of the bulking agent and the binder, the temperature is slowly increased at a lower heating rate, which can reduce the temperature difference inside the material, make the inside of the calcined material more uniform, and avoid the generation of defects.
[0029] The present invention further provides a porous graphite material prepared according to the above preparation method.
[0030] The porous graphite material has a uniform microstructure, a high open porosity, and a porosity that can be adjusted within a relatively large range of 30-50%. At the same time, the pores are interconnected.
[0031] According to some preferred embodiments of the present invention, by adjusting the size and proportion of the bulking agent particles, the porous graphite material obtained has a pore size of 5-55 μm and a bending strength greater than 35 MPa.
[0032] The present invention has the following beneficial effects: The bulking agent used in the present invention is a biomass material, which is cheap and has significant economic advantages, and the production process does not cause any environmental pollution; The preparation method of the present invention can accurately control the pore size, pore size distribution and porosity of the obtained porous graphite material; The porous graphite material obtained by the invention has high mechanical strength, narrow pore size distribution, uniform pore distribution and no internal defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Flow chart of the preparation of porous graphite material in the embodiment.
[0034] Figure 2 This is the SEM image of the porous graphite material obtained in Example 1.
[0035] Figure 3 This is the SEM image of the porous graphite material obtained in Example 2.
[0036] Figure 4 This is the SEM image of the porous graphite material obtained in Example 3. DETAILED DESCRIPTION
[0037] The technical scheme of the present invention will be further described below in conjunction with the embodiments and drawings of the present invention. The embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0038] Example 1 See attached Figure 1 , the porous graphite material is prepared by the following steps: (1) Grinding the raw materials, including: The calcined pitch coke with an ash content of 0.25%, a moisture content of 0.05%, a volatile matter content of 0.32%, and a carbon content of 99.4% was ground to obtain aggregate powder A with a D50 particle size of 20 μm; The asphalt having an ash content of 0.15%, a moisture content of 0.12%, a quinoline insoluble content of 3.8%, and a softening point of 118°C was ground to obtain a binder B having a D50 particle size of 10 μm; Starch with a moisture content of 0.06% dried at 120°C was ground to obtain a bulking agent C with a D50 particle size of 45 μm; (2) Mixing and kneading, including: Weigh 63% and 37% of aggregate powder A and binder B, respectively. Add aggregate powder A into a kneader for dry mixing. When the dry mixing temperature reaches 185°C, add binder B for wet mixing. The wet mixing time is 2h and the wet mixing temperature is 220-250°C. Cool the mixture out of the pot to obtain paste D, whose volatile matter content is 12.4%. Weigh 85% and 15% of bulking agent C and binder B respectively, add bulking agent C into a kneader for dry mixing, add binder B for wet mixing when the dry mixing temperature reaches 225°C, the wet mixing time is 0.5h, the wet mixing temperature is 220-240°C, and cool out of the pot to obtain coating material E; (3) Secondary grinding, including: The paste D is ground to obtain a paste powder E having a D50 particle size of 145 μm; The coated material E is ground to obtain coated powder F with a D50 particle size of 65 μm; (4) Mixing: Weigh 40% and 60% of the paste powder E and coating powder F respectively, add them into a V-type mixer and mix for 1.5 hours to obtain pressed powder H; (5) Green forming: The pressed powder H is placed in a rubber film sleeve, sealed and evacuated, and then put into an isostatic press to obtain a green body K. The isostatic pressing pressure is 140 MPa. (6) Calcination: The green body K was placed in a crucible, which was filled with yellow sand for protection, and was roasted in a roasting furnace at a pressure of 4.0 MPa to obtain porous carbon M. The roasting process was as follows: the temperature was increased from room temperature to 200°C at a heating rate of 20°C / h, from 200°C to 350°C at a heating rate of 3°C / h, from 350°C to 550°C at a heating rate of 4°C / h, from 550°C to 750°C at a heating rate of 8°C / h, from 750°C to 950°C at a heating rate of 12°C / h, and kept at 950°C for 8h, then cooled from 950°C to 600°C at a cooling rate of 45°C / h, and then naturally cooled to room temperature. (7) Graphitization: The porous carbon M is loaded into a vacuum graphitization furnace for graphitization treatment to obtain a porous graphite material S, wherein the graphitization process is as follows: heating from room temperature to 750°C at a heating rate of 115°C / h, heating from 750°C to 1350°C at a heating rate of 75°C / h, heating from 1350°C to 1600°C at a heating rate of 50°C / h, heating from 1600°C to 1900°C at a heating rate of 30°C / h, heating from 1900°C to 2400°C at a heating rate of 70°C / h, and keeping warm for 6 hours, followed by natural cooling.
[0039] The obtained porous graphite material was characterized by microstructure, and the obtained SEM image is shown in the attached figure. Figure 2 As shown, it can be seen that the internal pores of the material are well developed, the pore size distribution is narrow, the larger bulking agent forms a larger pore size, the average pore size is 55 microns, channels are formed between the pores, and the particles are closely connected, so that the material maintains a high mechanical strength.
[0040] Example 2 See attached Figure 1 , the porous graphite material is prepared by the following steps: (1) Grinding the raw materials, including: The calcined pitch coke with an ash content of 0.25%, a moisture content of 0.05%, a volatile matter content of 0.32%, and a carbon content of 99.4% was ground to obtain aggregate powder A with a D50 particle size of 15 μm; The asphalt having an ash content of 0.15%, a moisture content of 0.12%, a quinoline insoluble content of 3.8%, and a softening point of 118°C was ground to obtain a binder B having a D50 particle size of 10 μm; Starch with a moisture content of 0.06% dried at 120°C was ground to obtain a bulking agent C with a D50 particle size of 25 μm; (2) Mixing and kneading, including: Weigh 55% and 45% of aggregate powder A and binder B respectively, add aggregate powder A into a kneader for dry mixing, add binder B for wet mixing when the dry mixing temperature reaches 185°C, the wet mixing time is 1h, the wet mixing temperature is 220-250°C, cool out of the pot to obtain paste D, the volatile matter content of which is 14.7%; Weigh 75% and 25% of bulking agent C and binder B respectively, add bulking agent C into a kneader for dry mixing, add binder B for wet mixing when the dry mixing temperature reaches 225°C, the wet mixing time is 0.5h, the wet mixing temperature is 220-240°C, and cool out of the pot to obtain coating material E; (3) Secondary grinding, including: The paste D is ground to obtain a paste powder E having a D50 particle size of 55 μm; The coated material E is ground to obtain coated powder F having a D50 particle size of 32 μm; (4) Mixing: Weigh 60% and 40% of the paste powder E and coating powder F respectively, add them into a V-type mixer and mix for 1.5 hours to obtain pressed powder H; (5) Green forming: The pressed powder H is placed in a rubber film sleeve, sealed and evacuated, and then put into an isostatic press to obtain a green body K. The isostatic pressing pressure is 150 MPa. (6) Calcination: The green body K was loaded into a crucible, which was filled with yellow sand for protection, and was roasted in a roasting furnace at a pressure of 4.5 MPa to obtain porous carbon M. The roasting process was as follows: the temperature was increased from room temperature to 200°C at a heating rate of 10°C / h, from 200°C to 350°C at a heating rate of 2°C / h, from 350°C to 550°C at a heating rate of 3°C / h, from 550°C to 750°C at a heating rate of 6°C / h, from 750°C to 950°C at a heating rate of 8°C / h, and kept at 950°C for 12h, then cooled from 950°C to 600°C at a cooling rate of 30°C / h, and then naturally cooled to room temperature. (7) Graphitization: The porous carbon M is loaded into a vacuum graphitization furnace for graphitization treatment to obtain a porous graphite material S, wherein the graphitization process is as follows: heating from room temperature to 750°C at a heating rate of 80°C / h, heating from 750°C to 1350°C at a heating rate of 50°C / h, heating from 1350°C to 1600°C at a heating rate of 30°C / h, heating from 1600°C to 1900°C at a heating rate of 15°C / h, heating from 1900°C to 2400°C at a heating rate of 50°C / h, and keeping warm for 6 hours, followed by natural cooling.
[0041] The obtained porous graphite material was characterized by microstructure, and the obtained SEM image is shown in the attached figure. Figure 3 As shown, it can be seen that the smaller bulking agent particles inside the material form smaller pores with an average pore size of 30 microns. The particles and pore sizes are evenly distributed, and the particles are more tightly bound together.
[0042] Example 3 See attached Figure 1 , the porous graphite material is prepared by the following steps: (1) Grinding the raw materials, including: The calcined pitch coke with an ash content of 0.25%, a moisture content of 0.05%, a volatile matter content of 0.32%, and a carbon content of 99.4% was ground to obtain aggregate powder A with a D50 particle size of 18 μm; The asphalt having an ash content of 0.15%, a moisture content of 0.12%, a quinoline insoluble content of 3.8%, and a softening point of 118°C was ground to obtain a binder B having a D50 particle size of 10 μm; Starch with a moisture content of 0.06% dried at 120°C was ground to obtain a bulking agent C with a D50 particle size of 30 μm; (2) Mixing and kneading, including: Weigh 60% and 40% of aggregate powder A and binder B respectively, add aggregate powder A into a kneader for dry mixing, add binder B for wet mixing when the dry mixing temperature reaches 185°C, the wet mixing time is 1.5h, the wet mixing temperature is 220-250°C, and cool out of the pot to obtain paste D, whose volatile matter content is 13.8%; Weigh 80% and 20% of the bulking agent C and binder B respectively, add the bulking agent C into the kneader for dry mixing, add the binder B for wet mixing when the dry mixing temperature reaches 225°C, the wet mixing time is 1 hour, the wet mixing temperature is 220-240°C, and cool out of the pot to obtain the coating material E; (3) Secondary grinding, including: Grinding the paste D to obtain a paste powder E with a D50 particle size of 100 μm; The coated material E is ground to obtain coated powder F having a D50 particle size of 45 μm; (4) Mixing: Weigh 45% and 55% of the paste powder E and coating powder F respectively, add them into a V-type mixer and mix for 1.5 hours to obtain pressed powder H; (5) Green forming: The pressed powder H is placed in a rubber film sleeve, sealed and evacuated, and then put into an isostatic press to obtain a green body K. The isostatic pressing pressure is 145 MPa. (6) Calcination: The green body K was placed in a crucible, which was filled with yellow sand for protection, and was roasted in a roasting furnace at a pressure of 4.3 MPa to obtain porous carbon M. The roasting process was as follows: the temperature was increased from room temperature to 200°C at a heating rate of 10°C / h, from 200°C to 350°C at a heating rate of 3°C / h, from 350°C to 550°C at a heating rate of 4°C / h, from 550°C to 750°C at a heating rate of 7°C / h, from 750°C to 950°C at a heating rate of 10°C / h, and kept at 950°C for 10 hours, then cooled from 950°C to 600°C at a cooling rate of 40°C / h, and then naturally cooled to room temperature. (7) Graphitization: The porous carbon M is loaded into a vacuum graphitization furnace for graphitization treatment to obtain a porous graphite material S, wherein the graphitization process is as follows: heating from room temperature to 750°C at a heating rate of 100°C / h, heating from 750°C to 1350°C at a heating rate of 65°C / h, heating from 1350°C to 1600°C at a heating rate of 40°C / h, heating from 1600°C to 1900°C at a heating rate of 20°C / h, heating from 1900°C to 2400°C at a heating rate of 60°C / h, and keeping warm for 4 hours, followed by natural cooling.
[0043] The obtained porous graphite material was characterized by microstructure, and the obtained SEM image is shown in the attached figure. Figure 4As shown, it can be seen that the surface of the sample block is polished and smooth, and the distribution of micropores inside the material can be visually observed. The pore diameter is between that of Example 1 and Example 2, and the average pore diameter is 40 microns.
[0044] The performance parameters of the porous graphite materials obtained in Examples 1-3 were tested, and the results are shown in Table 1: Table 1
[0045] It can be seen that the size of the average pore size is related to the size of the fluffing agent particles. The larger the fluffing agent particles, the larger the internal pore size of the material. The compressive strength and flexural strength of the material are affected by the coarseness of the aggregate particles. Reducing the aggregate particles is beneficial to improving the mechanical strength of the material.
[0046] It should be noted that the above is only a preferred embodiment of the present invention, which should not limit the protection scope of the technical solution of the present invention. Any modification of the technical solution recorded in the above embodiments and equivalent replacement of technical features by ordinary technicians in the field within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a porous graphite material, characterized in that: It includes: (1) Grinding the calcined asphalt coke to obtain aggregate powder, grinding the asphalt to obtain a binder, and grinding the dry starch to obtain a bulking agent; (2) kneading the aggregate powder with the first part of the binder to obtain a first paste, and kneading the bulking agent with the second part of the binder to obtain a first coating material; (3) grinding the first paste to obtain a second paste, and grinding the first coating material to obtain a second coating material; (4) mixing the second paste and the second coating material to obtain compressed powder; (5) isostatically pressing the pressed powder to obtain a green body; (6) calcining the green body to obtain a porous carbon material; (7) graphitizing the porous carbon material to obtain a porous graphite material; Among them, the D50 particle size of the aggregate powder is 15-20μm; the D50 particle size of the binder is 8-12μm; the D50 particle size of the bulking agent is 20-50μm; the D50 particle size of the second paste is 50-150μm; the D50 particle size of the second coating material is 20-70μm; in the first paste, the mass content ratio of the aggregate powder to the first part of the binder is 50-65%:50-35%; in the first coating material, the mass content ratio of the bulking agent to the second part of the binder is 75-85%:25-15%; in the pressed powder, the mass content ratio of the second paste to the second coating material is 30-65%:70-35%.
2. The preparation method according to claim 1, characterized in that: in, The kneading process for obtaining the first paste includes: dry mixing the aggregate powder until the dry mixing temperature reaches above 180°C, adding the first part of the binder, wet mixing at 220-250°C for 1-2h, and then cooling to obtain the first paste. The volatile matter content of the first paste obtained after kneading is 12-15%.
3. The preparation method according to claim 1, characterized in that: The kneading process for obtaining the first coating material includes: dry mixing the bulking agent until the dry mixing temperature reaches above 220° C., adding the second part of the binder, wet mixing at 220-240° C. for 0.5-1 h, and then cooling to obtain the first coating material.
4. The preparation method according to claim 1, characterized in that: The isostatic pressing pressure is 130-150 MPa.
5. The preparation method according to claim 1, characterized in that: The isostatic pressing comprises: placing the pressed powder into a rubber film sleeve, sealing it, evacuating it, and then pressing it through an isostatic press.
6. The preparation method according to claim 1, characterized in that: The method for obtaining the compressed powder includes: adding the second paste and the second coating material into a V-type mixer and mixing them for 1-1.5 hours.
7. The preparation method according to claim 1, characterized in that: The calcination comprises: placing the green body into a calcination crucible filled with yellow sand, and then calcining it in a calcination furnace.
8. The preparation method according to claim 1, characterized in that: The calcination comprises: at 4.0-4.5Mpa, heating from room temperature to 200°C at a heating rate of 10-20°C / h, then heating from 200°C to 350°C at a heating rate of 2-4°C / h, then heating from 350°C to 550°C at a heating rate of 3-5°C / h, then heating from 550°C to 750°C at a heating rate of 6-8°C / h, then heating from 750°C to 950°C at a heating rate of 8-12°C / h, keeping at 950°C for 6-12h, then cooling from 950°C to 600°C at a cooling rate of 30-50°C / h, and then naturally cooling to room temperature.
9. The preparation method according to claim 1, characterized in that: The graphitization treatment includes: heating from room temperature to 750°C at a heating rate of 80-120°C / h, heating from 750°C to 1350°C at a heating rate of 50-80°C / h, heating from 1350°C to 1600°C at a heating rate of 30-50°C / h, heating from 1600°C to 1900°C at a heating rate of 15-30°C / h, heating from 1900°C to 2400°C at a heating rate of 50-80°C / h, and keeping warm for 4-6h, followed by natural cooling.
10. The porous graphite material prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Porous carbon material and its preparation method
CN102417174A
Carbon material and method for producing same
CN102791628A
High-rebound-elasticity porous graphite material and preparation method thereof
CN104386669A
High-purity high-conductivity graphene graded porous carbon and preparation method thereof
CN108557799A
Porous breathable graphite as well as preparation method and application thereof
CN114988402A